Prediction of self-terminating Ventricular Tachycardia in isolated rat heart experiments by using wavelet analysis - Le Duy Manh,; Bui Phuong Thuy,; Bui Van Hai,; Man Minh Tan,; Trinh Xuan Hoang,; Chan, C. K.; Lai, Pik-Yin (Vietnam Journal of Science and Technology, 2024)
This study investigates whether self-terminating and prolonged ventricular tachycardias (VT) can be differentiated using cross-wavelet analysis. VT is a type of arrhythmia that may persist or transform into other arrhythmias. In this study, 40 VT samples from 7 isolated rat hearts are analyzed, including 19 prolonged VTs and 21 self-terminating VTs (STVTs). Bivariate timeseries of left ventricular and right atrium are analyzed using cross-wavelet analysis to find correlations between the signals. The results show that self-terminating VT occurs most frequently when there is a weak correlation between the signals, while prolonged VT is associated with a strong correlation between ventricular and atrial signals. The study suggests that mechano-electrical interaction between the right atrium and left ventricle may be the underlying mechanism for this connection. The findings may have implications for understanding the underlined mechanism and treatment of VT in clinical practice.